Social Loneliness, Emotional Loneliness and Loneliness in Love as Predictors of Life Satisfaction in Adolescents - Numanović, Almedina Š.; Smailović, Semrija Ć.; Mladenović, Željko J.; Murić, Nevzeta R. (Collection of Papers of the Faculty of Philosophy in Priština, 2023)
The primary aim of our research was to examine the impact of social loneliness, emotional loneliness and loneliness in love on life satisfaction of young people, including the variables of gender, age and material status. The study involved 200 high school students (86 female) from Novi Pazar, Serbia, 15–19 years old (M=16.76, SD=1.308). The data were collected through the scale of social loneliness, emotional loneliness and loneliness in love (SSELL) as a modified version of the scale of social and emotional loneliness among adults and the life satisfaction scale (LSS). Statistically significant impact of participants’ age, material status of the family, loneliness in family and loneliness in love on life satisfaction is established. Loneliness in love is the best predictor of life satisfaction. The greater the loneliness in love, loneliness in family and material status of the family, the lower the life satisfaction. The finding that the material status of the family contributes to better socialization and a higher degree of life satisfaction is counterintuitive, given that the higher the material status of the family, the lower the life satisfaction score. There is no social loneliness in the model which predicts life satisfaction. Gender differences in terms of variables which influence life satisfaction in adolescents were established. Loneliness in love has the greatest influence on life satisfaction for men, while for female respondents, loneliness in family comes first, followed by loneliness in love. Other variables which appear in the model in the case of the undivided sample do not appear in the analysis of the subsamples by gender.
Keywords: life satisfaction; loneliness; adolescents